Theory of Dark Energy (London Journal of Research In Science: Natural and Formal, 2025)
In the International Journal of Physics and Astronomy [1] a formula for calculation of dark energy was developed [1]. It is:Ed = (h/tp2) tu (1.2)In the Journal of Physics and AstronomyThe Foundations of a Dark Energy Theory was mentioned for the first time in my article Commentary about Calculation of Dark Energy and Dark Matter [2]In the article which is presented here, the Theory of Dark Energy is now completed and a physical-mathematical and theoretical derivation of the formula [1] is provided. This provides physical-mathematical and theoretical sopport for the formula [1] previously developed using a simple three-sentence operation.
Keywords: bivariate survival functions; dependence functions; biomedical applications; econometrics; bivariate Wiener and Pareto stochastic processes construction; dark energy.; PLANCK time; age of the universe